Effect of bond length on the behaviour of CFRP strengthened concrete-filled steel tubes under transverse impact. (15th November 2015) - Alam, Md Iftekharul; Fawzia, Sabrina; Liu, Xuemei
Abstract: Concrete-filled steel tubular (CFST) columns have shown great potential as axial load carrying member and used widely in many mission critical infrastructures. However, attention is needed to strengthen these members where transverse impact force is expected to occur due to vehicle collisions. In this work, finite element (FE) model of carbon fibre reinforced polymer (CFRP) strengthened CFST columns are developed and the effect of CFRP bond length is investigated under transverse impact loading. Initially the numerical models have been validated by comparing impact test results from literature. The validated models are then used for detail parametric studies by varying the length of externally bonded CFRP composites. The parameters considered for this research are impact velocity, impact mass, CFRP modulus, adhesive type, and axial static loading. It has been observed that the effect of CFRP strengthening is consistent after an optimum effective bond length of CFRP wrapping. The effect of effective bond length has been studied for above parameters. The results show that, under combined axial static and transverse impact loads CFST columns can successfully prevent global buckling failure by strengthening only 34% of column length. Therefore, estimation of effective bond length is essential to utilise the CFRP composites cost effectively.